METHODOLOGY FOR USING VIRTUAL EXCURSIONS IN PRIMARY SCHOOL NATURAL SCIENCE LESSONS - Zukhurova Rukhsorabonu Tolib kizi (International Journal of Literature and Language Studies, 2026)
The development of digital educational technologies has created new opportunities for organizing natural science lessons in primary education. One of these opportunities is the use of virtual excursions, which enable pupils to observe natural objects, ecosystems, museums, protected areas, laboratories, and geographical locations without leaving the classroom. This article examines the pedagogical and methodological foundations of using virtual excursions in primary school natural science lessons. It analyses the educational potential, structure, types, implementation stages, teaching methods, assessment criteria, and organizational conditions of virtual excursions. A three-stage methodology consisting of preparatory, implementation, and reflective-assessment phases is proposed. The article emphasizes that a virtual excursion should not be reduced to passive video watching. It must include a clearly defined learning objective, observation tasks, teacher guidance, interactive activities, group discussion, practical assignments, and reflection.